PENGARUH KOMPONEN-KOMPONEN FRAUD STAR TERHADAP KORUPSI DENGAN SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) SEBAGAI VARIABEL MODERASI - Ulfah apriani (Jurnal Magister Akuntansi Trisakti, 2020)
This study aims to examine the influence of fraud star components to corruption with the government internal control system (SPIP) as a moderation variable. The sample used in this study was 230 respondents to the Judges, Employees and Auditors of the Indonesian Supreme Court. The test is carried out using Structural Equation Modeling (SEM) analysis, the data is processed using Partial Least Square (PLS) on the Windows 10 version of the SmartPLS3.2.8. The result of the research shows that pressure has a positive effect on corruption, opportunity has a positive effect on corruption, rationalization has a positive effect on corruption, the ability to have a positive effect on corruption and integrity has a negatif effect on corruption. The government internal control system weakens the positive influence of pressure on corruption, the government internal control system does not weaken the positive influence of opportunity on corruption, the government internal control system does not weaken the positive influence of rationalization on corruption, the government internal control system does not weaken the positive influence of the ability to corruption and the internal control system the government does not strengthen the negative influence of integrity on corruption. The government internal control system (SPIP) in the Supreme Court of the Republic of Indonesia must be able to be adapted to the COSO theory because the Supreme Court is a government institution that has special charecteristics where as a law enforcer has the authority to decide a case.